CFD modeling of two-phase flow of a spillway chute aerator of large width. Issue 2 (2nd July 2016) - Teng, Penghua; Yang, James
Abstract : An aerator is frequently used to prevent cavitation damages in high-velocity spillways. To understand its characteristics, one often resorts to physical model tests. To complement physical model tests, computation fluid dynamics simulations are used to determine water–air flow behaviors. With Bergeforsen's 35 m wide aerator, numerical modeling has been performed to evaluate its performance and improve its configuration. The parameters of interest include spillway discharge capacity, air entrainment rate, duct subpressure and air concentration in the aerated flow. The simulated discharge capacity agrees reasonably with experimental data. Due to the larger chute width, empirical formulas do not reasonably predict the air demand. To provide the air required by the aerator, its distribution in the cavity must be guaranteed. We thus looked into the air supply system and the air flux in the cavity to improve the aerator function. Larger vent openings in the middle of the chute are preferable for large-width aerators.